The plant matrix of Artemisia annua L. for the treatment of malaria: Pharmacodynamic and pharmacokinetic studies - Fujie Xu; Xiaohang Shan; Jialin Li; Jing Li; Jiqiao Yuan; Daozeng Zou; Manyuan Wang (PLoS ONE, 2025)
Artemisinin-based combination therapies (ACTs) constitute the principal strategy for combating malaria in contemporary times, and research into the multifaceted components of Artemisia annua L. (A. annua) has garnered widespread interest among scientists. The aim of this study was to prepare A. annua extracts (nACTs) and to explore whether nACTs have higher bioavailability and efficacy than artemisinin (ART) alone due to its multiple bioactive components. Initially, the in vivo antimalarial activity of nACTs was evaluated by two murine malaria models. The results revealed that the antimalarial effect of nACTs was about 10-fold higher than that of ART alone when administered at the same dosage of ART. Then, we analyzed the pharmacokinetic characteristics of nACTs in rat plasma. Remarkably, nACTs exhibited significantly enhanced oral bioavailability, longer half-life as well as extended mean retention time in rats. In addition, the impact of nACTs on P-glycoprotein (P-gp) was evaluated using the Caco-2 cell line. The results showed that both ART and nACTs reduced the efflux rate of the P-gp substrate rhodamine 123 (R123) and induced the expression of P-gp in Caco-2 cells over a range of concentrations. nACTs had certain components-deoxyartemisinin (DEART), artemisinic acid (AA), and dihydroartemisinic acid (DHAA)-that inhibited the efflux and translocation of P-gp and facilitated the reduction of ART efflux. In conclusion, A. annua extracts significantly improved the antimalarial efficacy and bioavailability compared with ART.